Utilization of Digital Marketing in the Development of MSMEs in the Era of Digital Technology - Sofyan Hadinata (Penerbit Hellow Pustaka, 2023)
Digital marketing is a promotional and market search activity through digital media online by utilizing various means such as social networking. The virtual world is no longer only able to connect people with devices, but also people with others all over the world. The existence of MSMEs is expected to be able to spur the economy amid the economic slowdown that is happening today. The utilization of digital technology-based marketing concept (digital marketing) provides hope for MSMEs to develop into a center of economic power. MSMEs actors collaborate with digital-based promotional media and distribution media to earn the maximum profit. Today, almost all MSMEs businesses or even restaurant and fast food businesses use promotional media and digital marketing-based distribution media. Some businesses that tend to want to survive offline life are slowly experiencing setbacks. The type of food and drink business becomes the most widely held MSMEs business by MSMEs actors. Switching offline purchases into online (digital), will make it easier for MSMEs to expand marketing access. The role of digital technology has a significant influence on MSMEs. The emerging technology paradigm utilizes the stronger and sustainable potential of MSMEs. Social media and E-commerce can be a container of sale of MSMEs. It is known that MSMEs do not follow the maximum digital development, especially due to lack of knowledge about digital marketing.